Safety and efficacy of ruxolitinib in splanchnic vein thrombosis associated with myeloproliferative neoplasms. Issue 2 (February 2017) - Pieri, Lisa; Paoli, Chiara; Arena, Umberto; Marra, Fabio; Mori, Fabio; Zucchini, Mery; Colagrande, Stefano; Castellani, Alessandro; Masciulli, Arianna; Rosti, Vittorio; De Stefano, Valerio; Betti, Silvia; et al.
Abstract: Splanchnic vein thrombosis (SVT) is one of the vascular complications of myeloproliferative neoplasms (MPN). We designed a phase 2 clinical trial to evaluate safety and efficacy of ruxolitinib in reducing splenomegaly and improving disease‐related symptoms in patients with MPN‐associated SVT. Patients diagnosed with myelofibrosis (12 cases), polycythemia vera (5 cases) and essential thrombocythemia (4 cases) received ruxolitinib for 24 weeks in the core study period. Spleen volume was assessed by magnetic resonance imaging (MRI) and splanchnic vein circulation by echo‐Doppler analysis. Nineteen patients carried JAK2 V617F, one had MPL W515L, and one CALR L367fs*46 mutation. Eighteen patients had spleno‐portal‐mesenteric thrombosis, two had Budd–Chiari syndrome, and one had both sites involved; 16 patients had esophageal varices. Ruxolitinib was well tolerated with hematological toxicities consistent with those of patients without SVT and no hemorrhagic adverse events were recorded. After 24 weeks of treatment, spleen volume reduction ≥35% by MRI was achieved by 6/21 (29%) patients, and a ≥50% spleen length reduction by palpation at any time up to week 24 was obtained by 13/21 (62%) patients. At week 72, 8 of the 13 (62%) patients maintained the spleen response by palpation. No significant effect of treatment on esophageal varices or in splanchnic circulation was observed. MPN‐related symptoms, evaluated by MPN‐symptom assessment form (SAF) TSS questionnaire, improved significantly during the first 4 weeks and remained stable up to week 24. In conclusion, this trial shows that ruxolitinib is safe in patients with MPN‐associated SVT, and effective in reducing spleen size and disease‐related symptoms.